2013
DOI: 10.1038/pr.2013.77
|View full text |Cite
|
Sign up to set email alerts
|

Does congenital cytomegalovirus infection lead to hearing loss by inducing mutation of the GJB2 gene?

Abstract: Background: Congenital cytomegalovirus (CMV) infection and mutation of the gap junction β-2 (GJB2) gene are important causes of sensorineural hearing loss (SNHL). This study aims to determine if congenital CMV infection leads to deafness by inducing GJB2 mutation. Methods: GJB2 gene sequencing and auditory brainstem response testing were performed in 159 neonates (63 with and 96 without CMV infection) from August 2008 to August 2011. For neonates with GJB2 mutation, their parents were further screened for GJB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The findings of this study show that cytomegalovirus infection prior to conception may have effects on PTB. Combined with previous research results showing that maternal CMV infection during pregnancy might be a risk factor for adverse pregnancy/neonatal outcomes, and congenital cytomegalovirus infection may cause deafness in neonates [ 33 ], our analysis on the role of cytomegalovirus infection supports the suggestion that screening and treatment of CMV infection is accepted into the one of the pre-pregnancy health policies. A positive anti-CMV IgM result indicates a recent infection, and if reproductive-aged women are diagnosed with CMV infection in conjunction with clinical presentation, patient history, and other laboratory findings, doctors should advise some specific treatments or wait until after the anti-CMV IgM changed to negative before couples consider pregnancy.…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this study show that cytomegalovirus infection prior to conception may have effects on PTB. Combined with previous research results showing that maternal CMV infection during pregnancy might be a risk factor for adverse pregnancy/neonatal outcomes, and congenital cytomegalovirus infection may cause deafness in neonates [ 33 ], our analysis on the role of cytomegalovirus infection supports the suggestion that screening and treatment of CMV infection is accepted into the one of the pre-pregnancy health policies. A positive anti-CMV IgM result indicates a recent infection, and if reproductive-aged women are diagnosed with CMV infection in conjunction with clinical presentation, patient history, and other laboratory findings, doctors should advise some specific treatments or wait until after the anti-CMV IgM changed to negative before couples consider pregnancy.…”
Section: Discussionsupporting
confidence: 83%
“…A study by Liu et al (49) found that 79G>A, 341A>G, 109G>A, and 608T>C were common polymorphisms in the Dai and Han ethnic groups. A study by Li et al (50) detected GJB2 mutations in neonates and identified the 4 types of mutation they considered to be polymorphisms. Other studies have shown that 79G>A, 341A>G, and 608T>C are found in the general population but do not cause deafness (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…These CMV-induced changes could result in the already described mutations through changes in regulatory processes. This could also explain the involvement of the eyes that is sometimes present [ 76 ].…”
Section: Diagnostics and Causes Of Early Childhood Hearing Disordermentioning
confidence: 99%